2 Answers | Add Yours
The equation 5/12-5/6=x-3/2 has to be solved for x.
=> x = 5/12 - 5/6 + 3/2
=> x = 13/12
The solution of the equation 5/12-5/6=x-3/2 is x = 13/12
The method to solving this problem is to isolate x first by adding `3/2` on both sides.
`5/12-5/6=x-3/2` `=> 5/12-5/6+3/2 = x`
Then, in order to evaluate fractions that have a different denominator (value on the bottom of the fraction bar), we must find the denominators' lowest common multiple, which in this case is 12.
`5/12-5/6+3/2 = x => 5/12-5/6*2/2+3/2*6/6 = x`
We can do these multiplications because it is essentially multiplying by 1 and does not change the values in the equation. The above equation becomes:
`5/12-10/12+18/12 = x` which simplifies to `13/12 = x`
Therefore, `x = 13/12`
We’ve answered 288,465 questions. We can answer yours, too.Ask a question